Novel plasminogen activator inhibitor-1-derived peptide protects against impairment of cerebrovasodilation after photothrombosis through inhibition of JNK MAPK - Armstead, William M. (American Physiological Society, 2010)
The sole FDA-approved treatment for acute stroke is recombinant tissue-type plasminogen activator (rtPA). However, rtPA aggravates the impairment of cerebrovasodilation induced by global hypoxia/ischemia; this impairment is attenuated by the preinjury treatment with the plasminogen activator inhibitor derivative EEIIMD. MAPK (a family of kinases, p38, and JNK) is upregulated after cerebral ischemia. In this study, we determined whether the novel plasminogen activator inhibitor-derived peptide, Ac-RMAPEEIIMDRPFLYVVR-amide, (PAI-1-DP) given 30 min before or 2 h after, focal central nervous system injury induced by photothrombosis would preserve responses to cerebrovasodilators and the role of p38 and JNK MAPK in such effects. Cerebrospinal fluid JNK and p38 levels were elevated by photothrombotic injury, an effect potentiated by rtPA. Cerebrovasodilation was blunted by photothrombosis and reversed to vasoconstriction by rtPA but restored to dilation by PAI-1-DP pre- and posttreatment. PAI-1-DP blocked JNK, but preserved p38 MAPK upregulation after photothrombosis. The JNK MAPK antagonist SP600125 prevented, and the p38 antagonist SB203580 potentiated, impaired cerebrovasodilation after photothrombosis. These data indicate that rtPA impairs cerebrovasodilation after injury by activating JNK, while p38 MAPK is protective, and that the novel peptide PAI-1-DP protects by inhibiting activation of JNK by rtPA. JNK MAPK inhibitors, including PAI-1-DP, may offer a novel approach to increase the benefit-to-risk ratio of thrombolytic therapy and enable its use in central nervous system ischemic disorders.